Adaptations to a subterranean environment and longevity revealed by the analysis of mole rat genomes - Fang, Xiaodong; Seim, Inge; Huang, Zhiyong; Gerashchenko, Maxim V; Xiong, Zhiqiang; Turanov, Anton A; Zhu, Yabing; Lobanov, Alexei V; Fan, Dingding; Yim, Sun Hee; Yao, Xiaoming; Ma, Siming; et al. (Cell reports, 2014)
Subterranean mammals spend their lives in dark, unventilated environments that are rich in carbon dioxide and ammonia and low in oxygen. Many of these animals are also long-lived and exhibit reduced aging-associated diseases, such as neurodegenerative disorders and cancer. We sequenced the genome of the Damaraland mole rat (DMR, Fukomys damarensis) and improved the genome assembly of the naked mole rat (NMR, Heterocephalus glaber). Comparative genome analyses, along with the transcriptomes of related subterranean rodents, revealed candidate molecular adaptations for subterranean life and longevity, including a divergent insulin peptide, expression of oxygen-carrying globins in the brain, prevention of high CO2-induced pain perception, and enhanced ammonia detoxification. Juxtaposition of the genomes of DMR and other more conventional animals with the genome of NMR revealed several truly exceptional NMR features: unusual thermogenesis, an aberrant melatonin system, pain insensitivity, and unique processing of 28S rRNA. Together, these genomes and transcriptomes extend our understanding of subterranean adaptations, stress resistance, and longevity.
Keywords: Animals; RNA ribozomální 28S; termogeneze; RNA, Ribosomal, 28S; Melatonin; Genetic Speciation; Mole Rats; mikroftalmičtí podzemní hlodavci; sekvence aminokyselin; Molecular Sequence Data; genom; fyziologická adaptace; Genome; Insulin; Amino Acid Sequence; dlouhověkost; bolest; globiny; molekulární sekvence - údaje; Thermogenesis; aktiny; Actins; melatonin; Globins; Adaptation, Physiological; vznik druhů (genetika); Pain; ekosystém; Ecosystem; transkriptom; zvířata; Transcriptome; inzulin; Longevity